CURRENT ACCOUNTING PROBLEMS. - King, Earle C. (The Accounting Review, 1950)
Abstract The article focuses on the current accounting problems in the U.S. Most of the current problems arise in the appraising of transactions reflecting new methods of doing business or matters upon which there has been a wide difference of opinion among recognized accounting authorities for many years. Thorough analysis and discussion of the new problems and reappraisal of the old controversial problems are matters of mutual interest for all of us here, as well as for the registrants and certifying accountants directly concerned. Experience seems to indicate that most registrants and their independent public accountants prefer to have the financial statements and accountants' opinion contained in the report to stockholders in substantial agreement with the report to be filed with the U.S. Securities and Exchange Commission (SEC). There is no real difference in our requirements for disclosure of inconsistencies in accounting from those which prevailed in the accounting profession prior to the existence of the SEC.